Child Trafficking Offence: Case Study of Surabaya District Court Decision No. 685/PID.SUS/2022/PN SBY - Aini, Qurotu; Sodiqin, Ali; Yulianis, M Sifa Fauzi; Haniyah, Haniyah (Journal of Progressive Law and Legal Studies, 2023)
The emergence of various forms of manipulation and exploitation has resulted in rampant trafficking in persons, in which children are also trafficked. Basically, children as the next generation of the nation have a role in ensuring the continuity of the nation. Therefore, children need to get ample opportunities to grow and develop. This study was conducted with the aim of describing how legal protection of children as victims of trafficking in persons. The research method used in this study is normative legal research which is studied using a statutory approach (statute approach). The results of this study show that children are very vulnerable to becoming victims of child trafficking for the purpose of exploitation. The law relating to child trafficking has been in force and has binding legal force, but its enforcement has not been sufficient to provide a deterrent effect for perpetrators. In this case, children as victims should get legal protection which includes protection of their dignity, dignity, and fulfillment of their rights. However, in the criminal justice system, victims are often given less attention, in reality Indonesian law only focuses on punishing perpetrators and overrides the rights and protection of victims. Keywords: Child Trafficking.Exploitation. Legal Protection